L'affaire Galmot: Colonialism on trial in 1931. (August 2015) - Marsh, Kate
Between 9 March and 21 March 1931 12 men and two women, all French citizens from French Guiana, were put on trial at an extraordinary session of the cour d'assises in Nantes. All were accused of looting and murder during riots which had taken place on 6 and 7 August 1928 in Cayenne; all were acquitted. Despite being one of the biggest trials of the interwar period in France, the event was largely forgotten until a major exhibition staged in Nantes in 2011. Examining the public reaction to the trial in 1931, this article has two key aims. First, it will explore attitudes towards colonialism and republicanism in the provinces and metropolitan France. Second, it will use the exhibition of 2011 as a means of addressing the memorial debate to show how such recoveries of forgotten events, however laudable and necessary, risk perpetuating an image of an idealised republicanism based upon universalism.